Utilização de maturadores para antecipação da colheita do milho - Garcia, Rodolfo Apolinário de Faria [UNESP] (2014)
The aim of this study was to evaluate the effect of maturing in order to anticipate the corn harvest of Maximus hybrid. The products used were: trinexapac-ethyl and ethephon with 4 pre defined rates according to their use in other cultures (0.4 , 0.6, 0.8 and 1 L c.p. ha- 1) applied at two times (75 e 90 days after sowing - DAS), where each time was a experiment. The experiments were carried out in randomized blocks design with 3 replications in a factorial scheme 2x4+ T. It was evaluated the 100-grains mass, diameter and length of the ears, the produced mass of cob, the yield and the moisture of grains evaluated in three different times (137, 144 and 158 DAS). Treatments did not affect the characteristics of the 100-grain mass, diameter and length of ears, but when the application occurred at 75 DAS cob mass produced by plants of the control was 17 % more than that observed in plots which received treatment. The productivity was reduced in average by 10 % with the usage of ripeners, regardless of dosage, in the application held at 75 DAS, however for application realized on 90 DAS that there was no effect. The average of the grains moisture degree was different in all samples with the application made after 75 DAS. The trinexapac-ethyl provided less moisture compared to ethephon in all cases. For the second time of application, held at 90 DAS, there was no statistical difference between the treatments in the sample did at 144 DAS (17.1 and 17.8 % for trinexapac-ethyl and ethephon, respectively), but these differed from the control which presented high average of grains moisture in the treatments (19.0%). Finally is concluded that it is possible to antedate the corn harvest, with the application of trinexapac-ethyl and ethephon realized 90 DAS based on moisture results without interference in the corn yeild